The effect of the use of the Round Robin strategy in the acquisition of historical concepts among secondgrade intermediate students in the history course of social writers - Rasha Alwan Mahoud (Genius Journals, 2022)
The goal of the current research is to know (the effect of the Round Robin strategy in the acquisition of historical concepts among the second-grade students in history). The researcher chose the experimental approach, with partial control for two groups, one experimental and the other control, and selected a sample of second-grade female students from the Alkahl High School for Girls in Alkahl in Alkahl District in Maysan Governorate for the academic year (2021-2022), and randomly selected Division A to represent the experimental group of (40) students, and Division C to represent the (40)students, The researcher conducted an equivalence between the students of the two research groups in the following variables: intelligence test, time age calculated in months, social semester scores and the academic achievement of the parents. The researcher formulated behavioral goals, which reached (60) behavioral goals, and prepared teaching plans, where the number of plans reached (16) for the experimental group and(16)plan for the control group. The research goal also required the preparation of a test to acquire historical concepts of a type of multiple test consisting of (33) paragraphs, and the researcher used the following statistical methods: the test of two independent samples, a square KK2 and a coefficient of correlation of Pearson, the equation of the difficulty coefficient, the coefficient of excellence, and the equation of the effectiveness of false alternatives, and the researcher concluded after analyzing the results statistically superior to the student of the experimental group. The study of the history using the traditional method, the student of the subject and study The researcher came up with a set of conclusions, recommendations and proposals
Keywords: Round Robin strategy; acquisition; historical; proposals